PEMANFAATAN GOOGLE MAPS API UNTUK VISUALISASI DATA BASE TRANSCEIVER STATION - Septia Rani (Teknoin, 2016)
This paper discusses the use of the Google Maps API to perform data visualization for Base Transceiver Station (BTS) data. BTS are typically used by telecommunications companies to facilitate wireless communication between communication devices with the network operator. Each BTS has important information such as it’s location, it’s transaction traffic, as well as information about revenue. With the implementation of BTS data visualization using the Google Maps API, key information owned by each BTS can be presented more attractive and also easier to understand. BTS data visualization supports decision-making processes related to company policies such as marketing strategy in order to increase the revenue of the company